STRATEGIC PRIORITY ANALYSIS OF BAZNAS SANTRIPRENEUR FOR BUSINESS PERFORMANCE ENHANCEMENT (Jurnal Manajemen Pembangunan Daerah, 2026)
ABSTRACTThe Santripreneur Program by BAZNAS is a pesantren-based economic empowerment initiative aimed at enhancing the self-reliance of santri (Islamic boarding school students) through training, mentoring, and business support. However, there has been no strategic study that systematically maps the relative contribution of each program aspect and development strategy to the improvement of participants’ business performance. This study aims to determine the priority of program aspects and development strategies deemed most influential in this context. The method used is the Analytic Network Process (ANP) based on expert judgment. A total of seven expert respondents provided assessments of five clusters of program aspects including entrepreneurship training, cash assist, competition, business assistance, and monitoring and five development strategies. The results indicate that capital assistance is the highest-priority aspect, while the integration of training curriculum and sustainable mentoring schemes are the most recommended development strategies. These findings are expected to serve as a foundation for strategic decision-making by BAZNAS in developing the program more effectively and sustainably. Keywords: ANP, business performance, development strategy, pesantren entrepreneurship, Santripreneur.